Anticancer therapeutic effect of ginsenosides through mediating reactive oxygen species - Li, Xiaonan; Cao, Donghui; Sun, Siming; Wang, Yuehui (Frontiers in Pharmacology, 2023)
Dysregulation of reactive oxygen species (ROS) production and ROS-regulated pathways in cancer cells leads to abnormal accumulation of reactive oxygen species, displaying a double-edged role in cancer progression, either supporting transformation/proliferation and stimulating tumorigenesis or inducing cell death. Cancer cells can accommodate reactive oxygen species by regulating them at levels that allow the activation of pro-cancer signaling pathways without inducing cell death via modulation of the antioxidant defense system. Therefore, targeting reactive oxygen species is a promising approach for cancer treatment. Ginsenosides, their derivatives, and related drug carriers are well-positioned to modulate multiple signaling pathways by regulating oxidative stress-mediated cellular and molecular targets to induce apoptosis; regulate cell cycle arrest and autophagy, invasion, and metastasis; and enhance the sensitivity of drug-resistant cells to chemotherapeutic agents of different cancers depending on the type, level, and source of reactive oxygen species, and the type and stage of the cancer. Our review focuses on the pro- and anticancer effects of reactive oxygen species, and summarizes the mechanisms and recent advances in different ginsenosides that bring about anticancer effects by targeting reactive oxygen species, providing new ideas for designing further anticancer studies or conducting more preclinical and clinical studies.